Is it getting better? An analytical method to test trends in health disparities, with tobacco use among sexual minority vs. heterosexual youth as an example - Homma, Yuko (Int J Equity Health, 2016)
BACKGROUND: Previous studies have documented higher health risks for lesbian, gay, and bisexual youth compared to heterosexual youth. However, none has reported whether the sexual orientation-based gaps have widened, narrowed, or remained unchanged over time. The purpose of this study was to develop a way to test differences in trends between sexual minority and heterosexual youth cohorts in population-based studies, with cigarette smoking as an exemplar. METHODS: We analysed the Minnesota Student Survey of 1998–2010, a repeated, cross-sectional census of adolescent health in grades 9 and 12. Our sample was students with recent sexual experience (Ns = 17,376–19,617). Sexual orientation was measured by gender of sexual partners in the past 12 months: students with only opposite-gender partner(s) (OPPOS), students with both male and female partners (BOTH), students with only same-gender partner(s) (SAME). We used logistic regressions to examine trends in prevalence of past-month cigarette smoking from 1998 to 2010, separately for each orientation group. We then applied novel interaction analyses to test whether disparities in smoking prevalence between OPPOS and SAME/BOTH changed over time. RESULTS: Recent smoking rates decreased over time among all orientation groups. BOTH adolescents were more likely than OPPOS adolescents to report past 30-day smoking, but there were no significant differences between SAME adolescents and OPPOS adolescents. Year-by-orientation interactions indicated the gap between BOTH adolescents and OPPOS adolescents widened from 1998 to 2004, then persisted between 2004 and 2010. No significant interaction effects were observed between SAME adolescents and OPPOS adolescents. CONCLUSIONS: All orientation groups had decreasing trends in recent cigarette smoking; however, disparities in smoking rates remain between heterosexual adolescents and bisexual adolescents. These results provide a new method of not just documenting trends within minority groups, but examining whether health equity is improving for them compared to dominant groups.